Chabani Manganyi: Black intellectual and psychologist - Hayes, Grahame (PINS-Psychology in Society, 2016)
Chabani Manganyi’s work over many years now has caught the attention of discerning readers and critical scholars alike, and so a new book by him is certain to be anticipated with much interest. In his latest book, Apartheid and the making of a Black psychologist, he turns his biographical craft, that he has become renowned for, on himself. Manganyi starts his memoir telling us about his childhood growing up in Mavambe (what is now Limpopo province), and ends it with his years spent in the service of higher education, first as vice chancellor of the University of the North, and then as the director general of education under Mandela’s presidency. Impressive as these commitments to the cause of higher education in South Africa are, yet what really distinguishes Chabani Manganyi is the slew of excellent texts that he has produced since his early thirties (starting with the seminal Being-black-in-the-world in 1973; and then 1977a; 1977b; 1981; 1983; 1990; 1991; 1996; 2004a; 2004b; 2010; 2012; 2016), covering, amongst other things, the psychosocial intricacies of black subjectivity (especially within the constraints of apartheid social relations), through to wonderful biographies of Es’kia Mphahlele, Gerard Sekoto, and Dumile Feni.